(untitled) (Global Journal of Management and Business Research, 2022)
We are witnessing a revolutionary development of electronic banking due to the extremely fast growth of information technology, but also due to the growing momentum of the health pandemic from 2020. Electronic banking is our reality and will be here for the foreseeable future. Digitization is nothing new for banks, because they operate in a highly competitive environment, and service users are a generation that is highly technologically aware and requires quickly available information. The Corona pandemic has accelerated the already upward trends of digital transformation of banks. Electronic banking, as electronic handling of all types of banking transactions, primarily over the Internet, besides being simple, fast, inexpensive, available 24/7, it is also safer for the customers.